Reading Kannada Syllables - G, Purushothama (Journal of All India Institute of Speech and Hearing)
Reaction times for reading Kannada syllables were found for adult subjects. It was possible to vary the number of phonemes and the number of critical visual features representing phonemes independently to a certain extent. It was found that both of them influence the processing speed of syllables. Phonemes seem to affect the processing time more than the number of visual features that they are represented by.